PENGEMBANGAN MEDIA BAHAN AJAR BUKU ISLAM DALAM PEMBELAJARAN AKU HAMBA ALLAH UNTUK ANAK KELOMPOK A DI RA MUNIR ISMAIL SEPANJANG GONDANGLEGI-MALANG - Nurhayati; Jannah, Sinta Nur (JURALIANSI: Jurnal Lingkup Anak Usia Dini, 2022)
The development of science and technology has become an effective educational facility. The purpose of the research is to describe the form of media, learning I am a servant of Allah, and the results of the development of media for teaching Islamic books at RA Munir Islamil Sepanjang. The research method used by R n D includes defining, designing, developing, and disseminating. The results of the study describe product development through curriculum studies and the problem of needs for students in terms of clear mapping of indicators/sub-indicators/materials. Then, the manufacturing process can pay attention to the theme and content of the book, storyline, storyboard, making illustration designs, coloring and layout. One of the themes raised in the lesson I am a servant of God. The results of the development in the due diligence by media experts were 95.5 and the evaluation by material experts was 54.6. Conclusions and suggestions in BKSRA development research were very effective in providing more tangible benefits. Educators can redevelop in digital form. The combination of media in the form of visual and audio is mutually sustainable.